Special issue Cassandra's curse : the law and foreseeable future disasters - Sarat, Austin (Bingley, U.K. : Emerald, 2015)
This special issue of Studies in law, politics, and society examines the relationship between law and disasters. The papers come from members of the Collaborative Research Network on the Jurisprudence of Disasters within the Law and Society Association. This network was formed in 2012 at a conference held by the International Institute for the Sociology of Law, titled "Workshop on Disasters and Sociolegal Studies." The volume addresses the 'myths' of contemporary disaster law and policy, such as that of society's "invincibility". The papers examine specific cases such as the Fukushima Nuclear Disaster, bushfire management in Australia and wildfire prevention in the Mediterranean, as well as providing broader analysis and comment on global disaster law and policy.
Introduction : the myths we live (and die) by / Lloyd Burton, Lisa Grow Sun -- The "Cassandra zone" and law's moral purpose / Lloyd Burton -- Symbolic, cognitive, and structural obstacles to formulating disaster policy / Justin Pidot -- Foreseeable disaster mismanagement in a changing climate / Lisa Grow Sun, Sabrina McCormick -- Disaster assistance and legal accountability : care and surveillance / Susan Sterett -- Cassandra, Prometheus, and hubris : the epic tragedy of Fukushima / Masayuki Murayama, Lloyd Burton -- Bushfires and Australian emergency management law and policy : adapting to climate change and the new fire and emergency management environment / Michael Eburn -- The multi-level prevention and control of catastrophic wildfires in Mediterranean Europe : the European Union, Spain, and Catalonia / Juli Ponce ... [et al.].
Print version record
Keywords: Law -- General; Social Science -- Disasters & Disaster Relief; Law & society; Social impact of disasters; Disasters -- Law and legislation